Análise das condições de salubridade ambiental dos municípios com potencial turístico do litoral norte paraibano - Barbosa Segundo, Inalmar Dantas (2015)
Environmental sanitation is related to environmental sanitation services and is one of the most important to achieving a satisfactory human quality of life and, as well as adequate socioeconomic and cultural policies, should normally be provided by the government. In the same way that economics and ecology, environment and development, demonstrating an economy in which it is a social enterprise and the effort to preserve and regenerate the natural services on which Human survival depends, become decisive. In this way, the present work seeks to agglutinate referring to the relation of environmental health of a population, including the criteria to prioritize actions that improve tourism. The use of the Environmental Health Indicator next to the Indicator of Forested Areas (IAF) and the Indicator of Non-Urbanized Beaches (IPNU) was important for a more appropriate analysis of the municipalities of the northern coast of the state of Paraíba, mainly not with regard to the activity Tourist, which in this region is most sought after by sun and sea tourism. Thus, it was verified that the average of the Environmental Health Indicator for the municipalities was 40.09, showing a reality of low sanitation, at the same time as the Indicator of Non-Urbanized Beaches for median, with a value of 51.91 , And that of Forest Areas had a low result of 29.23. It is noticed that an urbanization is directly linked to a poor quality of the beaches, since as beaches with better balneabilidad of the municipalities also are like that practices free of the presence of direct anthropic occupation. Thus, these results indicate lack of interest and updating of public power that seek to serve the interest of the local community and the maintenance of its environmental patrimony. Thus, it was not indicated the promotion of tourism, without buildings of municipalities and suppliers of a better infrastructure of basic sanitation in order to present a good salubrity for its population and its visitors. The achievement of similar work or research in the coming years becomes essential to identify theoretical instruments that wish to continue guiding a tourism research agenda in the region studied, as well as the proposal of conceptual representations of intervention that lead to the integrated management of municipalities In question.